Toleration, Diversity, and Global Justice - Tan, Kok-Chor, 1964- (Book collections on Project MUSE., 2000)
"The "comprehensive liberalism" defended in this book offers an alternative to the narrower "political liberalism" associated with the writings of John Rawls. By arguing against making tolerance as fundamental a value as individual autonomy, and extending the reach of liberalism to global society, it opens the way for dealing more adequately with problems of human rights and economic inequality in a world of cultural pluralism."--Jacket.